Full-complex-phase ceramic flux-cored wire for in-situ generation of carbon titanium boride and preparation method of full-complex-phase ceramic flux-cored wire
By using in-situ generation of titanium carbon boronide fully composite ceramic flux core welding wire in arc spraying technology, combined with ceramic reinforcement materials, the problem of ceramic materials being difficult to completely melt and unevenly distributed in the thermal spraying process of ceramic coating is solved, and the coating performance with high hardness, wear resistance and high temperature resistance is achieved, which significantly improves the comprehensive performance of ceramic matrix composite coating.
Patent Information
- Application Number
- CN202510166878.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-14
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-02-14
AI Technical Summary
During the thermal spraying process, the existing arc spraying ceramic coatings have problems such as difficulty in completely melting the ceramic materials, uneven distribution of ceramic phases, and weak bonding between coatings, resulting in the impact of coating performance and the ceramic phase content is relatively small. The comprehensive performance of the coating, especially the high-temperature wear resistance, cannot reach the level of ceramic matrix composite coatings.
In situ, a fully composite ceramic flux-core welding wire of titanium carbode is used to form ceramic flux-core welding wire with high hardness, high wear resistance and high temperature resistance by reasonably preparing the chemical components of the melted metal in the flux-core welding wire, including boron, carbon, silicon, manganese, copper, chromium, titanium, cerium and iron, to form ceramic phases with high hardness, high wear resistance and high temperature resistance, and combine ceramic reinforcement materials such as zirconium oxide and aluminum carbide to improve the overall performance of the coating.
The high hardness, wear resistance and high temperature resistance of flux-core welding wire is achieved. The Rockwell hardness is greater than 67HRC, the Vickers hardness is maintained at 850℃ not less than 650HV10, the wear resistance is more than 4.6 times that of Cr26 high chromium cast iron, and the comprehensive performance of the coating is significantly improved, solving the problem of insufficient performance of ceramic matrix composite coating.
Smart Images

Figure CN119870786A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of material processing and welding materials, and particularly relates to an in-situ generated titanium carboride full-complex ceramic flux-cored welding wire and a preparation method thereof. Background Art
[0002] Titanium carboboride is an important boride material with excellent physical and chemical properties. Titanium carboboride has an oxidation resistance temperature of up to 1000°C in air, is stable in HCl and HF acid, and has good chemical stability, wear resistance and conductivity. Therefore, titanium carboboride is widely used in many fields. For example, it can be used to manufacture rocket nozzles, electrical contacts and high-temperature electrode materials. In addition, it can also be combined with other materials to form composite materials for wire drawing dies, extrusion dies, sandblasting nozzles, sealing elements, cutting tools, armor protection and other materials. However, titanium carboboride also has the defects of high hardness, high brittleness and low toughness, which makes it easy to break when impacted or stressed, limiting its further application in industry. For this reason, a lot of research has been conducted on improving the performance of titanium carboboride, and the concept of titanium carboboride full-phase ceramics has been proposed.
[0003] Arc spraying technology has the advantages of high efficiency, low cost, and suitability for on-site and large-area construction. It is the lowest cost and most suitable for large-scale promotion among thermal spraying technologies. However, the principle of arc spraying determines that it can only be used to spray conductive low-melting point metal wires at first, and it is difficult to directly obtain high-performance ceramic coatings with high melting point, high hardness, high wear resistance, and non-conductivity. Compared with solid wires, arc spray powder core wires have the advantages of both outer skin and inner core materials. They not only overcome the difficulty of wire drawing with high alloy or intermetallic compound components, but also enable non-conductive ceramic granular materials to be filled into the core, making arc spraying technology successfully applied to the preparation of ceramic, metal ceramic and intermetallic compound coatings, broadening the application field of arc spray coating materials and promoting the rapid development of arc spraying technology.
[0004] At present, arc sprayed ceramic coatings are mostly prepared by directly filling and spraying ceramic materials in the core. There are prominent problems in the spraying process, such as difficulty in completely melting the ceramic material, uneven distribution of the ceramic phase, and weak bonding between the coating layers, which have a significant adverse effect on the coating performance. Alternatively, a small amount of reaction components are added to the metal or alloy, and the ceramic phase is synthesized by reaction during the spraying process to obtain a hard phase particle-reinforced metal-based composite coating to improve the coating's wear resistance, high temperature resistance and other properties. However, due to the small content of the ceramic phase, the comprehensive performance of the coating, especially the high temperature wear resistance, still cannot reach or approach that of a ceramic-based composite coating with ceramic as the main body.
[0005] Based on this, the present invention provides an in-situ generated titanium carboride full-complex phase ceramic flux-cored welding wire with high hardness, wear resistance and high temperature resistance. Summary of the invention
[0006] One object of the present invention is to provide an in-situ generated titanium carbide boride full-complex ceramic flux-cored welding wire, and another object of the present invention is to provide a preparation method of the in-situ generated titanium carbide boride full-complex ceramic flux-cored welding wire.
[0007] To achieve the first purpose of the present invention, the following technical solution is adopted:
[0008] An in-situ generated titanium carboride full-complex ceramic flux-cored welding wire, the flux-cored welding wire comprises an outer sheath and a flux core filled in the outer sheath, and the chemical composition of the deposited metal of the flux-cored welding wire, measured by weight percentage, comprises the following components:
[0009] Boron: 2.8-4.2%; Carbon: 1.2-2.3%; Silicon: 0.5-1.5%; Manganese: 1.5-3.0%; Copper: 0.4-1.3%; Chromium: 3-6%; Titanium: 1.2-3.0%; Cerium: 0.2-0.7%; The balance is iron.
[0010] The present invention will be further described below:
[0011] In the present invention, each chemical component of the deposited metal of the flux-cored welding wire has a corresponding function, which is as follows:
[0012] The role of the boron (B) element is to strengthen the matrix and generate a hard phase, thereby making the flux-cored welding wire have a phase with high hardness and high melting point.
[0013] The role of the carbon (C) element is to strengthen the matrix and generate a hard phase, thereby making the flux-cored wire have a phase with high hardness and high melting point.
[0014] The role of silicon (Si) is to strengthen the matrix and stitch the grain boundaries, making the grain boundaries between the grains in the flux-cored welding wire more regular and tight, thereby improving the strength, plasticity and toughness of the flux-cored welding wire.
[0015] The role of manganese (Mn) element is to strengthen and toughen the matrix, thereby improving the strength and toughness of the flux-cored wire, absorbing the energy generated by the flux-cored wire during surfacing, and reducing the generation and expansion of cracks.
[0016] The role of copper (Cu) element is to refine the grains, purify the structure, and improve the weld strength and corrosion resistance of the flux-cored welding wire.
[0017] The role of chromium (Cr) element is to neutralize and optimize the affinity between the matrix and the reinforcement, reduce the crack tendency, and thus reduce the occurrence of cracks in the flux-cored welding wire.
[0018] The role of titanium (Ti) element is to refine the grains, enhance the initial nucleation of the high hardness reinforcement phase, enhance the promotion effect on the formation of acicular ferrite structure in the deposited metal, and improve the toughness of the deposited metal.
[0019] The function of cerium (Ce) element is to refine the grains, purify the structure, improve the toughness and strength of the weld, and at the same time it can also improve the stability of the arc, reduce spatter and improve the formation of the weld.
[0020] Preferably, the chemical composition of the deposited metal of the flux-cored welding wire comprises the following components by weight percentage:
[0021] Boron: 3.5%; Carbon: 1.7%; Silicon: 1.0%; Manganese: 2.3%; Copper: 0.8%; Chromium: 4.5%; Titanium: 2.1%; Cerium: 0.5%; Iron: 83.6%.
[0022] Preferably, the flux-cored welding wire comprises the following components in parts by weight:
[0023] 4.2-6.2 parts of boron carbide; 1.1-2.0 parts of graphite; 0.8-2.3 parts of 75% ferrosilicon alloy; 1.7-3.4 parts of electrolytic manganese; 0.4-1.3 parts of pure copper; 4.3-8.5 parts of high carbon ferrochrome; 2-5 parts of 70% ferrotitanium powder; 1.1-3.8 parts of cerium oxide; 2.5-2.9 parts of iron powder.
[0024] More preferably, the flux-cored welding wire comprises the following components in parts by weight:
[0025] 5.2 parts of boron carbide; 1.5 parts of graphite; 1.5 parts of 75% ferrosilicon alloy; 2.6 parts of electrolytic manganese; 0.8 parts of pure copper; 6.4 parts of high carbon ferrochrome; 3.5 parts of 70% ferrotitanium powder; 0.8 parts of cerium oxide; 2.7 parts of iron powder.
[0026] In the present invention, the sources of the chemical components of the deposited metal of the flux-cored welding wire are different, and this is further explained:
[0027] Boron exists in the form of boron carbide, which has high wear resistance, high hardness and good chemical stability. Adding boron carbide can improve the hardness and wear resistance of flux-cored welding wire;
[0028] Carbon exists in the form of graphite. Graphite has high temperature resistance and can improve the high temperature resistance of flux-cored welding wire. Therefore, it can be used as the main source of carbon in flux-cored welding wire.
[0029] Silicon exists in the form of 75% ferrosilicon alloy. Silicon atoms combine with iron atoms to form silicon-containing ferrite with strong covalent bonds, which not only promotes the formation of ferrite, but also significantly strengthens the ferrite. The combination of the two improves the strength, plasticity and toughness of the flux-cored welding wire. Therefore, 75% ferrosilicon alloy is used as the source of silicon in the flux-cored welding wire.
[0030] Manganese exists in the form of electrolytic manganese, which has high strength and hardness, as well as certain plasticity and toughness, and can improve the strength, hardness and toughness of flux-cored welding wire, and can provide more manganese elements for flux-cored welding wire;
[0031] Copper exists in the form of pure copper, which can improve the strength and hardness of the weld and enhance the load-bearing capacity of the weld. Therefore, it is used as the source of copper in flux-cored welding wire;
[0032] Chromium exists in the form of high-carbon ferrochrome, which has good chemical stability, wear resistance and high hardness, and can improve the wear resistance and hardness of flux-cored welding wire. Therefore, it is used as the source of chromium in flux-cored welding wire.
[0033] Titanium exists in the form of 70% ferrotitanium powder. By directly adding different amounts of ferrotitanium to the powder of gas-shielded flux-cored welding wire, titanium is transitioned to the deposited metal under argon-rich and CO2 shielding gas welding conditions, and inclusions such as MnO-TiOx-Al2O3-SiO2 composite oxides can be generated. The presence of these inclusions helps to promote the formation of acicular ferrite structure, thereby improving the toughness of the deposited metal. At the same time, the addition of 70% ferrotitanium powder can refine the grains, increase the hardness of the weld, and improve the impact toughness. This is because titanium can combine with elements such as oxygen and nitrogen to form stable compounds, reducing the influence of harmful impurities. Therefore, 70% ferrotitanium powder is used as the source of titanium in flux-cored welding wire.
[0034] Cerium exists in the form of cerium oxide, which can be used as an arc stabilizer, which can stabilize the welding arc and reduce the fluctuation of the arc, thereby improving the stability of the welding process, helping to reduce spatter, and improving welding efficiency and weld quality; at the same time, cerium oxide has a strong reducing property, which can react with oxygen during welding to play a deoxidation role, helping to prevent the formation of oxide inclusions in the weld and improve the mechanical properties and corrosion resistance of the weld; furthermore, cerium oxide can react metallurgically with other elements in the weld to improve the chemical composition and mechanical properties of the weld metal, such as promoting the refinement of the weld metal and improving the toughness and strength of the weld; in addition, cerium oxide can decompose at high temperatures to produce gases, which can provide partial or most of the protection to prevent the weld metal from being oxidized by oxygen and nitrogen in the air during welding. Therefore, cerium oxide is used as the source of cerium in flux-cored welding wire.
[0035] Iron exists in the form of iron powder, which can increase the deposition rate in flux-cored welding wire and combine with other metals to form a weld with certain strength and toughness.
[0036] Preferably, the flux-cored welding wire also includes a ceramic reinforcement material, which is a mixture of zirconium oxide and aluminum carbide, and the added mass ratio of the zirconium oxide and the aluminum carbide is 3:1. During the formation of the Mo2FeB2 ternary boride hard phase of the zirconium oxide and aluminum carbide mixture, the aluminum carbide and zirconium oxide particles will melt and aggregate together, and be dispersed in the generated ceramic phase, thereby effectively improving the hardness and wear resistance of the surfacing metal.
[0037] Preferably, the outer skin is a low-carbon steel strip with a thickness of 0.4 mm and a width of 14 mm.
[0038] Preferably, the diameter of the flux-cored welding wire is 1.6 mm.
[0039] Preferably, the filling rate of the medicine powder in the medicine core is 20-30%, and more preferably, the filling rate of the medicine powder is 25%.
[0040] To achieve the second purpose of the present invention, the following technical solution is adopted:
[0041] A method for preparing an in-situ generated titanium carboride full-complex ceramic flux-cored welding wire comprises the following steps:
[0042] Step 1, add the components of the core in accordance with the formula in a drying machine at a temperature of 180-220°C in sequence, dry for 2-3 hours, put into a three-dimensional motion mixer to mix thoroughly, and then put into an incubator at a temperature of 140-160°C to keep warm, and the obtained core powder is set aside;
[0043] Step 2, placing the outer skin on a flux-cored wire forming machine, and rolling the outer skin steel strip into a U-shaped groove by the forming machine;
[0044] Step 3: adding the flux core powder into the U-shaped groove, and the forming machine rolls and closes the U-shaped groove after adding the flux core powder and pulls it to obtain a flux cored welding wire.
[0045] Preferably, the temperature in the three-dimensional motion mixer is 200°C.
[0046] Ceramic-based composite materials are composite materials made through a composite process using ceramic materials as a matrix and high-strength fibers, whiskers, chips and particles as reinforcements. They are usually also called complex ceramic materials or multiphase composite ceramic materials. Since ceramic materials have the advantages of high strength, high hardness, high temperature resistance, and good high-temperature wear resistance, the present invention utilizes the advantages of ceramic materials to develop a flux-cored welding wire with high hardness, high temperature resistance and wear resistance. The flux-cored welding wire of the present invention is a full-complex ceramic flux-cored welding wire that is generated in situ, that is, a reinforcing phase such as titanium carboride TiB2 is generated internally during the reaction process. It overcomes the defects of coarse reinforcement particle size, thermodynamic instability, and low interface bonding strength in externally added composite materials.
[0047] Beneficial effects of the present invention:
[0048] ① In the present invention, the flux-cored welding wire has the characteristics of high hardness and wear resistance. The Rockwell hardness of the flux-cored welding wire of the present invention is greater than 67HRC; the Vickers hardness of the flux-cored welding wire of the present invention maintains the Vickers hardness of HV at 850°C. 10 Not less than 650, indicating high temperature resistance; the wear resistance of the flux-cored welding wire of the present invention is 4.6 times that of Cr26 high chromium cast iron; the metallographic structure of the flux-cored welding wire of the present invention shows a dispersed distribution of hard phases to form a high volume density reinforcement phase, and no coarse crack defects are observed.
[0049] ② The preparation method of the flux-cored welding wire of the present invention is simple and is conducive to industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 The metallographic structure diagram and microhardness test diagram of single-layer surfacing of flux-cored welding wire of Example 1 of the present invention;
[0051] Figure 2 The metallographic structure diagram and microhardness test diagram of single-layer surfacing of flux-cored welding wire in Example 2 of the present invention. DETAILED DESCRIPTION
[0052] The present invention can be further understood by the specific examples of the present invention given below, but they are not intended to limit the present invention.
[0053] Example 1
[0054] This embodiment 1 provides an in-situ generated titanium carbide and boride full-complex ceramic flux-cored welding wire, the flux-cored welding wire comprising an outer skin and a flux core filled in the outer skin, wherein the outer skin is a low-carbon steel strip with a thickness of 0.4 mm and a width of 14 mm, and the chemical composition of the deposited metal of the flux-cored welding wire, measured by weight percentage, includes the following components: boron: 2.8%; carbon: 1.2%; silicon: 0.5%; manganese: 1.5%; copper: 0.4%; chromium: 3%; titanium: 1.2%; cerium: 0.2%; iron 89.2%.
[0055] In the present embodiment 1, the powder filling rate in the flux core is 20%, and the diameter of the flux cored welding wire is 1.6 mm.
[0056] In this embodiment 1, boron B is obtained from boron carbide; carbon C is obtained from graphite; silicon Si is obtained from 75% ferrosilicon alloy; manganese Mn is obtained from electrolytic manganese; copper Cu is obtained from pure copper; chromium Cr is obtained from high carbon ferrochrome; titanium Ti is obtained from 70% ferrotitanium powder; cerium Ce is obtained from cerium oxide; and iron Fe is obtained from iron powder.
[0057] The preparation steps of the in-situ generated titanium carboride full-complex ceramic flux-cored welding wire of Example 1 are as follows:
[0058] Step 1, add 4.2 parts of boron carbide, 1.1 parts of graphite, 0.8 parts of 75% ferrosilicon alloy, 1.7 parts of electrolytic manganese, 0.4 parts of pure copper, 4.3 parts of high carbon ferrochrome, 2 parts of 70% ferrotitanium powder, 1.1 parts of cerium oxide and 2.9 parts of iron powder in a drying machine at a temperature of 180°C and bake for 2 hours, then put them into a three-dimensional motion mixer at a temperature of 200°C and mix them evenly, then put them into an incubator at a temperature of 140°C to keep them warm, and the obtained core powder is used for standby;
[0059] Step 2, placing a low-carbon steel strip with a thickness of 0.4 mm and a width of 14 mm on a flux-cored welding wire forming machine, and rolling the low-carbon steel strip into a U-shaped groove by the forming machine;
[0060] Step 3: Add flux core powder to the U-shaped groove. The forming machine rolls and closes the U-shaped groove after adding the flux core powder and pulls it to a welding wire diameter of 1.6 mm to obtain a flux cored welding wire.
[0061] like Figure 1 As shown, the metallographic structure of Example 1 is characterized by dispersed distribution of hard phase to form a high volume density reinforcement phase to obtain a high hardness deposited metal, and no coarse crack defects are observed.
[0062] Example 2
[0063] This embodiment 2 provides an in-situ generated titanium carbide and boride full-complex ceramic flux-cored welding wire, the flux-cored welding wire comprising an outer skin and a flux core filled in the outer skin, wherein the outer skin is a low-carbon steel strip with a thickness of 0.4 mm and a width of 14 mm, and the chemical composition of the deposited metal of the flux-cored welding wire, measured by weight percentage, includes the following components: boron: 3.5%; carbon: 1.7%; silicon: 1.0%; manganese: 2.3%; copper: 0.8%; chromium: 4.5%; titanium: 2.1%; cerium: 0.5%; iron: 83.6%.
[0064] In the present embodiment 2, the powder filling rate in the flux core is 25%, and the diameter of the flux cored welding wire is 1.6 mm.
[0065] In this embodiment 2, boron B is obtained from boron carbide; carbon C is obtained from graphite; silicon Si is obtained from 75% ferrosilicon alloy; manganese Mn is obtained from electrolytic manganese; copper Cu is obtained from pure copper; chromium Cr is obtained from high carbon ferrochrome; titanium Ti is obtained from 70% ferrotitanium powder; cerium Ce is obtained from cerium oxide; and iron Fe is obtained from iron powder.
[0066] The preparation steps of the in-situ generated titanium carboride full-complex ceramic flux-cored welding wire of Example 2 are as follows:
[0067] Step 1, 5.2 parts of boron carbide, 1.5 parts of graphite, 1.5 parts of 75% ferrosilicon alloy, 2.6 parts of electrolytic manganese, 0.8 parts of pure copper, 6.4 parts of high carbon ferrochrome, 3.5 parts of 70% ferrotitanium powder, 0.8 parts of cerium oxide and 2.7 parts of iron powder are sequentially added into a dryer at a temperature of 200°C and dried for 2.5 hours, and then put into a three-dimensional motion mixer at a temperature of 200°C and fully mixed, and then put into an incubator at a temperature of 150°C for insulation, and the obtained core powder is used for standby;
[0068] Step 2, placing a low-carbon steel strip with a thickness of 0.4 mm and a width of 14 mm on a flux-cored welding wire forming machine, and rolling the low-carbon steel strip into a U-shaped groove by the forming machine;
[0069] Step 3: Add flux core powder to the U-shaped groove. The forming machine rolls and closes the U-shaped groove after adding the flux core powder and pulls it to a welding wire diameter of 1.6 mm to obtain a flux cored welding wire.
[0070] like Figure 2 As shown, the metallographic structure of Example 2 is characterized by dispersed distribution of hard phase to form a high volume density reinforcement phase to obtain a high hardness deposited metal, and no coarse crack defects are observed.
[0071] Example 3
[0072] This embodiment 3 provides an in-situ generated titanium carbide and boride full-complex ceramic flux-cored welding wire, the flux-cored welding wire comprising an outer skin and a flux core filled in the outer skin, wherein the outer skin is a low-carbon steel strip with a thickness of 0.4 mm and a width of 14 mm, and the chemical composition of the deposited metal of the flux-cored welding wire, measured by weight percentage, includes the following components: boron: 4.2%; carbon: 2.3%; silicon: 1.5%; manganese: 3.0%; copper: 1.3%; chromium: 6%; titanium: 3.0%; cerium: 0.7%; iron 78%.
[0073] In the present embodiment 3, the powder filling rate in the flux core is 30%, and the diameter of the flux cored welding wire is 1.6 mm.
[0074] In this embodiment 3, boron B is obtained from boron carbide; carbon C is obtained from graphite; silicon Si is obtained from 75% ferrosilicon alloy; manganese Mn is obtained from electrolytic manganese; copper Cu is obtained from pure copper; chromium Cr is obtained from high carbon ferrochrome; titanium Ti is obtained from 70% ferrotitanium powder; cerium Ce is obtained from cerium oxide; and iron Fe is obtained from iron powder.
[0075] The preparation steps of the in-situ generated titanium carboride full-complex ceramic flux-cored welding wire of Example 3 are as follows:
[0076] Step 1, add 6.2 parts of boron carbide, 2.0 parts of graphite, 2.3 parts of 75% ferrosilicon alloy, 3.4 parts of electrolytic manganese, 1.3 parts of pure copper, 8.5 parts of high carbon ferrochrome, 5 parts of 70% ferrotitanium powder, 3.8 parts of cerium oxide and 2.5 parts of iron powder in a drying machine at a temperature of 220°C for 3 hours, put them into a three-dimensional motion mixer at a temperature of 200°C and mix them evenly, then put them into an incubator at a temperature of 160°C for insulation, and the obtained core powder is used for standby;
[0077] Step 2, placing a low-carbon steel strip with a thickness of 0.4 mm and a width of 14 mm on a flux-cored welding wire forming machine, and rolling the low-carbon steel strip into a U-shaped groove by the forming machine;
[0078] Step 3: Add flux core powder to the U-shaped groove. The forming machine rolls and closes the U-shaped groove after adding the flux core powder and pulls it to a welding wire diameter of 1.6 mm to obtain a flux cored welding wire.
[0079] No coarse crack defects were observed in the flux-cored welding wire of Example 3.
[0080] Example 4
[0081] Embodiment 4 provides an in-situ generated titanium carbide boride full-complex ceramic flux-cored welding wire, the flux-cored welding wire comprising an outer skin and a flux core filled in the outer skin, wherein the outer skin is a low-carbon steel strip with a thickness of 0.4 mm and a width of 14 mm, and the chemical composition of the deposited metal of the flux-cored welding wire, measured by weight percentage, includes the following components: boron: 3.5%; carbon: 1.7%; silicon: 1.0%; manganese: 2.3%; copper: 0.8%; chromium: 4.5%; titanium: 2.1%; cerium: 0.5%; zirconium: 0.2%; aluminum: 0.1% and iron: 83.3%.
[0082] In the present embodiment 4, the powder filling rate in the flux core is 25%, and the diameter of the flux cored welding wire is 1.6 mm.
[0083] In this embodiment 4, boron B is obtained from boron carbide; carbon C is obtained from graphite; silicon Si is obtained from 75% ferrosilicon alloy; manganese Mn is obtained from electrolytic manganese; copper Cu is obtained from pure copper; chromium Cr is obtained from high carbon ferrochrome; titanium Ti is obtained from 70% ferrotitanium powder; cerium Ce is obtained from cerium oxide; zirconium Zr is obtained from zirconium oxide, aluminum Al is obtained from aluminum carbide; and iron Fe is obtained from iron powder.
[0084] The preparation steps of the in-situ generated titanium carboride full-complex ceramic flux-cored welding wire of Example 4 are as follows:
[0085] Step 1, 5.2 parts of boron carbide, 1.5 parts of graphite, 1.5 parts of 75% ferrosilicon alloy, 2.6 parts of electrolytic manganese, 0.8 parts of pure copper, 6.4 parts of high carbon ferrochrome, 3.5 parts of 70% ferrotitanium powder, 2.7 parts of cerium oxide, 0.3 parts of zirconium oxide, 0.1 parts of aluminum carbide and 2.7 parts of iron powder are sequentially added into a dryer at a temperature of 200°C and dried for 2.5 hours, and then put into a three-dimensional motion mixer at a temperature of 200°C and fully mixed, and then put into an incubator at a temperature of 150°C for insulation, and the obtained core powder is used for standby;
[0086] Step 2, placing a low-carbon steel strip with a thickness of 0.4 mm and a width of 14 mm on a flux-cored welding wire forming machine, and rolling the low-carbon steel strip into a U-shaped groove by the forming machine;
[0087] Step 3: Add flux core powder to the U-shaped groove. The forming machine rolls and closes the U-shaped groove after adding the flux core powder and pulls it to a welding wire diameter of 1.6 mm to obtain a flux cored welding wire.
[0088] No coarse crack defects were observed in the flux-cored welding wire of Example 4.
[0089] Example 5
[0090] Wear resistance test
[0091] According to the loose abrasive wear test method of JB / T 7705-1995, the wear resistance of the flux-cored welding wires prepared in Examples 1-4 and the Cr26 high chromium cast iron sold on the market was tested by the rubber wheel method. The test results are shown in Table 1.
[0092] Table 1 Wear resistance test results
[0093] Test Group Initial mass m1 / g Mass after wear m2 / g Wear loss△m / g Example 1 65.187 65.137 0.050 Example 2 65.195 65.147 0.048 Example 3 65.198 65.146 0.052 Example 4 65.181 65.135 0.046 Cr26 high chromium cast iron 65.204 64.983 0.221
[0094] Example 6
[0095] Hardness performance test
[0096] According to the test methods in GB / T 230.1-2009 Rockwell hardness test for metal materials and GB / T 4340.1-2009 Vickers hardness test for metal materials, the flux-cored welding wires prepared in Examples 1-4 were subjected to Rockwell hardness performance tests and Vickers hardness performance tests, and the test results are shown in Table 2 and Table 3, respectively.
[0097] Table 2 Rockwell hardness performance test results
[0098] Test Group Example 1 Example 2 Example 3 Example 4 Rockwell hardness HRC 67.6 67.7 67.4 67.9
[0099] Table 3 Vickers hardness performance test results
[0100] Test Group Example 1 Example 2 Example 3 Example 4 <![CDATA[Vickers hardness HV at 850 °C 10 > 655 661 652 663
[0101] Analyze the results of Tables 1-3 above:
[0102] From the results in Table 1, it can be seen that the wear weight loss of the flux-cored welding wires prepared in Examples 1-4 is significantly lower than the wear weight loss of Cr26 high chromium cast iron, among which the wear weight loss of Cr26 high chromium cast iron is 4.6 times the wear weight loss of the flux-cored welding wire prepared in Example 2 (multiple = wear weight loss of Cr26 high chromium cast iron ÷ wear weight loss of the flux-cored welding wire in Example 2).
[0103] From the results in Table 2, it can be seen that the Rockwell hardness of the flux-cored welding wires prepared in Examples 1-4 is greater than 67HRC.
[0104] From the results in Table 3, it can be seen that the Vickers hardness of the flux-cored welding wires prepared in Examples 1-4 can still be maintained at more than 650 HV at a temperature of 850°C. 10 .
[0105] From the results in Table 1-3, it can be seen that by comparing the results of Example 4 with those of Example 1-3, under the same conditions, the wear resistance, Rockwell hardness and Vickers hardness of Example 4 are better than those of Example 1-3. The difference between Example 4 and Example 1-3 is that a ceramic reinforcement material obtained by mixing zirconium oxide and aluminum carbide is added to Example 4. In the process of forming the Mo2FeB2 ternary boride hard phase of the mixture of zirconium oxide and aluminum carbide, the aluminum carbide and zirconium oxide particles will melt and aggregate together, and be dispersed in the generated ceramic phase, thereby effectively improving the hardness and wear resistance of the surfacing metal.
[0106] The above is only an implementation method of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this field, some improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. An in-situ generated titanium carboride full-complex ceramic flux-cored welding wire, the flux-cored welding wire comprising an outer skin and a flux core filled in the outer skin, characterized in that: The chemical composition of the deposited metal of the flux-cored welding wire includes the following components by weight percentage: Boron: 2.8-4.2%; Carbon: 1.2-2.3%; Silicon: 0.5-1.5%; Manganese: 1.5-3.0%; Copper: 0.4-1.3%; Chromium: 3-6%; Titanium: 1.2-3.0%; Cerium: 0.2-0.7%; the balance is iron.
2. The in-situ generated titanium carboride full-complex ceramic flux-cored welding wire according to claim 1, characterized in that: The chemical composition of the deposited metal of the flux-cored welding wire includes the following components by weight percentage: Boron: 3.5%; Carbon: 1.7%; Silicon: 1.0%; Manganese: 2.3%; Copper: 0.8%; Chromium: 4.5%; Titanium: 2.1%; Cerium: 0.5%; Iron: 83.6%.
3. The in-situ generated titanium carboride full-complex ceramic flux-cored welding wire according to claim 1, characterized in that: The flux-cored welding wire comprises the following components in parts by weight: 5.2 parts of boron carbide; 1.5 parts of graphite; 1.5 parts of 75% ferrosilicon alloy; 2.6 parts of electrolytic manganese; 0.8 parts of pure copper; 6.4 parts of high carbon ferrochrome; 70% titanium iron powder 3.5 parts; cerium oxide 0.8 parts; iron powder 2.7 parts.
4. The in-situ generated titanium carboride full-complex ceramic flux-cored welding wire according to claim 3, characterized in that: The flux-cored welding wire also includes a ceramic reinforcement material, which is a mixture of zirconium oxide and aluminum carbide, and the added mass ratio of the zirconium oxide to the aluminum carbide is 3:
1.
5. The in-situ generated titanium carboride full-complex ceramic flux-cored welding wire according to claim 1, characterized in that: The outer skin is a low-carbon steel strip with a thickness of 0.4 mm and a width of 14 mm.
6. The in-situ generated titanium carboride full-complex ceramic flux-cored welding wire according to claim 1, characterized in that: The diameter of the flux-cored welding wire is 1.6 mm.
7. The in-situ generated titanium carboride full-complex ceramic flux-cored welding wire according to claim 1, characterized in that: The filling rate of the medicine powder in the medicine core is 25%.
8. A method for preparing an in-situ generated titanium carboride full-complex ceramic flux-cored welding wire as claimed in any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: Step 1, add the components of the core in accordance with the formula in a drying machine at a temperature of 180-220°C in sequence, dry for 2-3 hours, put into a three-dimensional motion mixer to mix thoroughly, and then put into an incubator at a temperature of 140-160°C to keep warm, and the obtained core powder is set aside; Step 2, placing the outer skin on a flux-cored wire forming machine, and rolling the outer skin steel strip into a U-shaped groove by the forming machine; Step 3: adding the flux core powder into the U-shaped groove, and the forming machine rolls and closes the U-shaped groove after adding the flux core powder and pulls it to obtain a flux cored welding wire.
9. The method for preparing the in-situ generated titanium carboride full-complex ceramic flux-cored welding wire according to claim 8, characterized in that: The temperature in the three-dimensional motion mixer was 200°C.
Citation Information
Patent Citations
Hard-facing alloys having improved crack resistance
CN101421073A
A high boron iron-based wear-resistant flux-cored welding wire
CN102284806A
High-boron high-chromium wear-resistant surfacing flux-cored welding wire
CN102319968A
Iron-based overlaying flux-cored welding wire for abrasion-resistant belts of drill pipe joints
CN102581515A
Iron-based corrosion resistant wear resistant alloy and deposit welding material for obtaining the alloy
KR1020090045252A